Feeding spent hemp biomass to lactating dairy cows: Effects on performance, milk components and quality, blood parameters, and nitrogen metabolism - Agung Irawan; Gracia Maria Puerto-Hernandez; Hunter Robert Ford; Sebastiano Busato; Serkan Ates; Jenifer Cruickshank; Juliana Ranches; Charles T. Estill; Erminio Trevisi; Massimo Bionaz (Journal of Dairy Science, 2024)
ABSTRACT: The legalization of industrial hemp by the 2018 Farm Bill in the United States has driven a sharp increase in its cultivation, including for cannabinoid extraction. Spent hemp biomass (SHB), produced from the extraction of cannabinoids, can potentially be used as feed for dairy cows; however, it is still illegal to do so in the United States, according to the US Food and Drug Administration Center for Veterinary Medicine, due to the presence of cannabinoids and the lack of data on the effect on animals. To assess the safety of this byproduct as feed for dairy cows, late-lactation Jersey cows (245 ± 37 d in milk; 483 ± 38 kg body weight; 10 multiparous and 8 primiparous) received a basal total mixed ration (TMR) diet plus 13% alfalfa pellet (CON) or 13% pelleted SHB for 4 wk (intervention period [IP]) followed by 4 wk of withdrawal period (WP), where all cows received only the basal TMR during WP. The dry matter intake (DMI), body weight, body condition score, milk yield, milk components, and fatty acid profile, blood parameters, N metabolism, methane emission, and activity were measured. Results indicated that feeding SHB decreased DMI mainly due to the low palatability of the SHB pellet, as the cows consumed only 7.4% of the total TMR with 13.0% SHB pellet offered in the ration. However, milk yield was not affected during the IP and was higher than CON during the WP, leading to higher milk yield/DMI. Milk components were not affected, except for a tendency in decreased fat percentage. Milk fat produced by cows fed SHB had a higher proportion of oleate and bacteria-derived fatty acids than CON. The activity of the cows was not affected, except for a shorter overall lying time in SHB versus CON cows during the IP. Blood parameters related to immune function were not affected. Compared with CON, cows fed SHB had a lower cholesterol concentration during the whole experiment and higher β-hydroxybutyric acid during the WP, while a likely low-grade inflammation during the IP was indicated by higher ceruloplasmin and reactive oxidative metabolites. Other parameters related to liver health and inflammatory response were unaffected, except for a tendency for higher activity of alkaline phosphatase during IP and a lower activity of gamma-glutamyl transferase during WP in the SHB group versus CON. The bilirubin concentration was increased in cows fed SHB, suggesting a possible decrease in the clearance ability of the liver. Digestibility of the dry matter and protein and methane emission were not affected by feeding SHB. The urea, purine derivatives, and creatinine concentration in urine was unaffected, but cows fed SHB had higher N use efficiency and lower urine volume. Altogether, our data revealed a relatively low palatability of SHB affecting DMI with minimal biological effects, except for a likely low-grade inflammation, a higher N use efficiency, and a possible decrease in liver clearance. Overall, the data support the use of SHB as a safe feed ingredient for lactating dairy cows.